Whose Peace? Whose Neighbor? Ethical Discourses in Devotional Publications and the Challenge of Religious Pluralism - Ineke Marlien Tombeng; James Edward Lalira (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This article reports on a qualitative, normative theological study that employs contextual hermeneutics within a Christian social ethics framework to examine how the Renungan Harian Keluarga (RHK), a weekly devotional publication, of Gereja Masehi Injili di Minahasa (GMIM), in North Sulawesi province, Indonesia, constructs peace and neighborliness in Indonesia’s plural society. This study aims to analyze how RHK constructs ethical visions of “peace” and “neighbor” within Indonesia’s plural society. Using contextual hermeneutics within Christian social ethics, this study analyzes 38 weekly RHK editions published from January to October 2025. The findings reveal that RHK consistently affirms universal principles such as justice, love, and human dignity. Its practical application remains largely intra-communal. “Neighbor” is predominantly framed as fellow believers, and “peace” as ecclesial harmony, rarely extending to explicit engagement with others. The study concludes that RHK demonstrates strong internal ethics but limited public ethics, reflecting benevolent insularity rather than intentional inclusiveness. This gap calls for a devotional pedagogy that explicitly names the religious other as a neighbor, thereby equipping the congregants to embody Imago Dei and shalom in Indonesia’s diverse democracy. The article contributes to Christian social ethics and public theology, as well as to the sociology of religion, peace studies, and intergroup relations, by showing how everyday devotional texts shape moral imagination in plural democracies.